2014
DOI: 10.1097/brs.0000000000000082
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Biphasic Transcranial Electric Stimulation in Intraoperative Motor Evoked Potential Monitoring for Cervical Compression Myelopathy

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…At present, there have been lots of studies concerning the application of transcranial motor evoked potential (MEP) to cervical spine surgery, including the value of predicting postoperative neurological deficits 1,2 ; the optimal mode of electric stimulation 3 , and warning thresholds 4 and others. On the contrary, some controversies regarding the intraoperative monitoring also present in cervical surgery, including high false positive rate, 5 low efficiency 6,7 , and lack of reliable warning criteria for CCM.…”
mentioning
confidence: 99%
“…At present, there have been lots of studies concerning the application of transcranial motor evoked potential (MEP) to cervical spine surgery, including the value of predicting postoperative neurological deficits 1,2 ; the optimal mode of electric stimulation 3 , and warning thresholds 4 and others. On the contrary, some controversies regarding the intraoperative monitoring also present in cervical surgery, including high false positive rate, 5 low efficiency 6,7 , and lack of reliable warning criteria for CCM.…”
mentioning
confidence: 99%
“…Ukegawa et al . 17 have shown that biphasic stimulation with a constant-current stimulator is an effective TES-MEP monitoring method and may reduce measurement time. However, they only compared monophasic and biphasic stimulation with a constant-current stimulator and did not report on the effects of constant-voltage stimulators or monophasic stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore conclude that when using constant-current stimulators, it is necessary to switch the stimulation polarity to study muscle responses bilaterally in order to avoid the disadvantages of monophasic stimulation. Alternatively, it may be necessary to use biphasic stimulation 17 . We believe that this information is important for surgeons to maintain adequate intraoperative spinal cord monitoring to prevent spinal cord injury during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The major clinical characteristics and diagnosis of the population were showed in Table 1. Patients were eligible for this study when they met all the following inclusion criteria: (1) presenting with symptomatic CCM with at least 1 clinical sign of myelopathy; (2) evidence of objective CCM on a magnetic resonance image (MRI); (3) absence symptomatic lumbar stenosis or thoracic myelopathy; (4) no previous surgical treatment for CCM; (5) undergoing the same anesthesia regime. Patients' duration of symptoms and preop modified Japanese Orthopedic Association (mJOA) scores associated with MEP phenotypes were showed in Fig.…”
Section: Patientsmentioning
confidence: 99%
“…It is important to assess cervical cord function in patients with CCM during surgical treatment. Over the past decades, the majority of studies are concerning the application of intraoperative transcranial motor evoked potential (MEP) to detect impending spinal cord damage, early warning the operating team to take action to avoid injury in cervical spine surgery [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%